The Influence of the Seven Principles of Zakat Management on Service Effectiveness and Efficiency: An Empirical Study Using the PLS-SEM Approach - Kolopita, Sukriyendi; Anwar, Saiful; Aini, Nur; Yana Aditya, Mochammad; Amelia, Amie (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2025)
This study aims to analyze the influence of seven fundamental principles of zakat management—Islamic law, trustworthiness, benefit, justice, legal certainty, integration, and accountability—on the effectiveness and efficiency of zakat institutions in Indonesia. A quantitative method was employed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach with data obtained from 100 respondents representing various zakat management institutions. The findings reveal that all seven principles have a significant effect on the effectiveness and efficiency of zakat services, with a coefficient of determination (R²) of 0.822, indicating a strong explanatory power of the model. The predictive relevance value (Q²) of 0.645 also demonstrates high predictive validity. Among these, accountability, integration, and trustworthiness emerge as the most dominant factors. These results confirm that zakat governance grounded in Islamic principles and supported by accountable and integrated institutional systems can significantly enhance the performance and optimization of zakat distribution and utilization